Tracheal and main bronchial diverticula simulating pneumomediastinum following a motor vehicle collision - Ryan Thibodeau, MD, MPH; Keisha Warn, MBA, BA; Abtin Jafroodifar, MD; Atin Goel, MBBS; Ernest Scalzetti, MD; Swati Deshmane, MBBS (Radiology Case Reports, 2021)
Tracheal and bronchial diverticula are outpouchings arising from the trachea or bronchus. We present a case of a 35-year-old female who presented to the emergency department following a motor vehicle accident and was found to have multiple round, air-filled structures within the mediastinum on computed tomography of the thorax, concerning for pneumomediastinum. The patient had a negative fluoroscopic esophagography and subsequent imaging indicated tracheal and bronchial diverticula. While they are often asymptomatic and incidentally found, tracheal and bronchial diverticula may be misdiagnosed as pneumomediastinum, especially in the setting of blunt or penetrating trauma to the thorax.